Implementing a provisional overarching intervention for COVID-19 monitoring and control in the Brazil-Colombia-Peru frontier - Contreras, Matilde; Gomes Naveca, Felipe; Carvajal-Cortes, Jose Joaquin; Faviero, Guilherme F.; Saavedra, Jorge; Ruback dos Santos, Eduardo; Alves do Nascimento, Valdinete; Costa de Souza, Victor; Oliveira do Nascimento, Fernanda; Silva e Silva, Dejanane; Luz, Sérgio Luiz Bessa; Romero Vesga, Kelly Natalia; et al. (Frontiers in Public Health, 2024)
The challenge was to provide comprehensive health resources to a remote and underserved population living in the Brazil-Colombia-Peru border, amid the most disruptive global crisis of the century.In August 2021, Fundacao Oswaldo Cruz Amazonia (Fiocruz Amazonia) and partner collaborators implemented an overarching provisional program for SARS-CoV-2 detection and lineages characterization, training of laboratory personnel and healthcare providers, donation of diagnostic supplies and personal protective equipment, and COVID-19 vaccination. The expedition was conducted at the Port of Tabatinga, a busy terminal with an intense flux of people arriving and departing in boats of all sizes, located in the Amazon River basin. Local government, non-profit organizations, private companies, and other stakeholders supported the intervention.The expedition was accomplished in a convergence point, where migrant workers, traders, army personnel, people living in urban areas, and people from small villages living in riversides and Field Code Changed indigenous territories are in close and frequent contact, with widespread cross-border movement. Using a boat as a provisional lab and storage facility, the intervention provided clinical and laboratory monitoring for 891 participants; vaccination for 536 individuals; personal protective equipment for 200 healthcare providers; diagnostic supplies for 1,000 COVID-19 rapid tests; training for 42 community health agents on personal protection, rapid test execution, and pulse oximeter management; and hands-on training for four lab technicians on molecular diagnosis. Discussion: Our experience demonstrates that multilateral initiatives can counterweigh the scarcity of health resources in underserved regions. Moreover, provisional programs can have a long-lasting effect if investments are also provided for local capacity building.